2020
DOI: 10.2147/ijgm.s287115
|View full text |Cite
|
Sign up to set email alerts
|

<p><sup>18</sup>F-FDG PET–CT Diagnosis of Tuberculosis in Celiac Lymph Nodes</p>

Abstract: The special location of abdominal tuberculosis makes it difficult for biopsy, while its clinical and imaging characteristics make it indistinguishable from tumors. Here, we report a female patient that was initially misdiagnosed with pancreatic cancer, but eventually correctly diagnosed with tuberculosis in the celiac lymph nodes using 18 F-FDG PET-CT. She was 38 years old. Her main complaint was "deep abdominal pain and discomfort for nearly a month", accompanied by nausea and vomiting. Diagnosis of pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…While FDG-PET/CT has shown to be effective in assessing metabolic activity of pulmonary lesions, some studies have indicated that FDG-PET/CT is more efficient than CT in assessing extra-pulmonary involvement 86 . As 15% of TB patients present with extra-pulmonary disease, it is imperative to identify the most sensitive diagnostic techniques, as imaging characteristics can often make M. tuberculosis lesions indistinguishable from tumors 87 . For example, Mao et al have noted that the clinical and traditional imaging features of abdominal tuberculosis can mimic pancreatic cancer, and the location is often difficult to biopsy 87 .…”
Section: Tuberculosis Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While FDG-PET/CT has shown to be effective in assessing metabolic activity of pulmonary lesions, some studies have indicated that FDG-PET/CT is more efficient than CT in assessing extra-pulmonary involvement 86 . As 15% of TB patients present with extra-pulmonary disease, it is imperative to identify the most sensitive diagnostic techniques, as imaging characteristics can often make M. tuberculosis lesions indistinguishable from tumors 87 . For example, Mao et al have noted that the clinical and traditional imaging features of abdominal tuberculosis can mimic pancreatic cancer, and the location is often difficult to biopsy 87 .…”
Section: Tuberculosis Infectionsmentioning
confidence: 99%
“…As 15% of TB patients present with extra-pulmonary disease, it is imperative to identify the most sensitive diagnostic techniques, as imaging characteristics can often make M. tuberculosis lesions indistinguishable from tumors 87 . For example, Mao et al have noted that the clinical and traditional imaging features of abdominal tuberculosis can mimic pancreatic cancer, and the location is often difficult to biopsy 87 . In these circumstances, FDG-PET/CT imaging combined with tuberculin testing or latent TB serology can help elucidate the correct diagnosis and help patients avoid unnecessary procedures.…”
Section: Tuberculosis Infectionsmentioning
confidence: 99%
“…In addition, it can be used to monitor response to treatment and identify recurrence. 10 However, it is not widely available, especially in resource-limited settings as in our country.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Furthermore, isolated coeliac lymph node TB can mimic pancreatic neoplasms, lymphoma or metastatic cancer both clinically and radiologically. 9 , 10 TB at other sites or a contact history of TB can aid in arriving at a diagnosis but this is present in less than 30% of patients. 5 In addition, the chest x-ray shows evidence of pulmonary TB in only 10%–68.5%.…”
Section: Discussionmentioning
confidence: 99%